2005
DOI: 10.1111/j.1469-7998.2005.00023.x
|View full text |Cite
|
Sign up to set email alerts
|

Ranging behaviour, spatial organization and activity of the Malay civet (Viverra tangalunga) on Buton Island, Sulawesi

Abstract: To compare the morphometrics and ranging behaviour of the Malay civet Viverra tangalunga on Sulawesi with published data on Malay civets on Borneo, a trapping and a radio-telemetry study was carried out in the Kakenauwe and Lambasango Forest Reserves on Buton Island, Sulawesi. From June to September in 2001September in , 2002 and 2003, we obtained morphometric measurements from 32 Malay civets captured in box traps. Ten civets were radio-collared and home-range size, minimum daily distance travelled and diel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 22 publications
2
31
0
1
Order By: Relevance
“…Malay civets are solitary, omnivorous and primarily terrestrial, and mainly occur in primary and secondary forests, but are sometimes found in plantations and near villages that are adjacent to forests (Jennings and Veron, 2009). However, little is known about the natural history and ecology of this species, and only a few field studies have been conducted on Borneo (Macdonald and Wise, 1979;Nozaki et al, 1994;Heydon and Bulloh, 1996;Colon, 2002) and Sulawesi (Jennings et al 2006); no study has previously been undertaken on Peninsular Malaysia. This paper presents the results from the first radio telemetry study of the Malay civet on Peninsular Malaysia.…”
Section: Introductionmentioning
confidence: 96%
“…Malay civets are solitary, omnivorous and primarily terrestrial, and mainly occur in primary and secondary forests, but are sometimes found in plantations and near villages that are adjacent to forests (Jennings and Veron, 2009). However, little is known about the natural history and ecology of this species, and only a few field studies have been conducted on Borneo (Macdonald and Wise, 1979;Nozaki et al, 1994;Heydon and Bulloh, 1996;Colon, 2002) and Sulawesi (Jennings et al 2006); no study has previously been undertaken on Peninsular Malaysia. This paper presents the results from the first radio telemetry study of the Malay civet on Peninsular Malaysia.…”
Section: Introductionmentioning
confidence: 96%
“…Civets are nocturnal, and utilize day bed resting sites in dense forest or grassy areas (Colo´n 2002;Jennings et al 2006). To conserve tag battery life and obtain the highest resolution of relevant GPS fixes, collars were set to record 13 hourly GPS points from 18h00 until 06h00.…”
Section: Gps Collaring and Trackingmentioning
confidence: 99%
“…Weighing between 3-7 kg, V. tangalunga is a predominantly solitary and terrestrial small carnivore found throughout the Sundaic region of Southeast Asia (Payne and Francis 1985). Although several VHF studies have evaluated the spatial ecology of V. tangalunga (Nozaki et al 1994;Colo´n 2002;Jennings et al 2006Jennings et al , 2010, this study represents the first known application of GPS collars to the Viverridae family, and ultimately aimed to demonstrate the scientific and conservation value of GPS technology deployments on small carnivores.…”
Section: Introductionmentioning
confidence: 99%
“…Although many such research projects are funded by such institutions as the World Bank and have produced a large number of technical papers (e.g. Crabbe & Smith, 2006;Jennings, Seymour, & Dunstone, 2006;May, 2005), a significant contribution to the understanding of sustainability at the micro-level has been achieved through the use of volunteers working on small-scale scientific projects The concept of volunteering has a long and established history in many subject (Stebbins, 1992;Stebbins & Graham, 2004;Uriely, Reichel, & Ron, 2003) areas; the volunteering literatures closest to tourism are: leisure (Parker, 1992), sport (Coleman, 2002;Cuskelly & Harrington, 1997;Gratton & Kokolakakis, 1997;Sport England, 1996 and events (Johnston, Twynam, & Farrell, 1999;Ralston, Lumsdon, & Downward, 2005;Solberg, 2003). The literature linked to volunteer tourism is fragmented with studies spanning a range of topics, for example: culture (McIntosh & Zahra, 2005); cultural exchange (Lyons, 2003); spirituality (Zahra, 2006); pilgrimage (Mustonen, 2005;Singh & Singh, 2004); self (Wearing, 2002(Wearing, , 2003Wearing & Deane, 2003;Wearing & Neil, 2000); self development (Uriely et al, 2003); and environment and conservation (Broad, 2003;Ellis, 2003;Halpeny & Caissie, 2003;Ryan, Kaplan, & Grese, 2001;Weston, Fendley, Jewell, Satchell, & Tazaros, 2003).…”
Section: Introductionmentioning
confidence: 99%